"Whisper and Write Game” as Pre-Writing Activity to Enhance Descriptive Writing Proficiency of Indonesian Seventh Graders - Mustofa, Ahmad Yusuf; Wahyuni, Sri (JALL (Journal of Applied Linguistics and Literacy), 2024)
Pre-writing is a preparation process before writing where students gather ideas, organize information, and plan their writing so that pre-writing has a significant influence on student writing outcomes. This study aims to analyze the effect of using whisper and write games as students' pre-writing activities on the descriptive writing abilities of the seventh-grade students at MTs Mamba'us Sholihin Gresik. This research uses class action research (CAR). The results showed that the improvement was seen from the cycle I and cycle II learning that had been implemented, comparing between cycle I and cycle II. The increase in learning outcomes was 76.19%, the increase obtained from the evaluation results in the first cycle was 14.28% and the second cycle was 90.47%. the learning outcomes of the last cycle show that the mastery of learning exceeds the KKM of 75%. Based on the results of the study it was explained that the use of whispering and writing as pre-writing activity games can help to understand and improve students' skills in writing descriptive text. and this can be seen from the increase in the percentage of student scores in each cycle. and the application of CAR can help students achieve the KKM target. The author admits that the writing of this research has several limitations. The limitation of this study is the inappropriate timing of the research because many agendas clashed with the school, so it is hoped that further research can adjust the time to be appropriate.